Loss of Productivity Due to Heat Exposure among Iranian Outdoor Workers - MOHAMMAD REZA MONAZZAM ESMAEIL POUR (International Journal of Occupational Hygiene, 2016)
Introduction: Direct sunlight and increased heat load influence mental and physical health of workers negatively and result in performance impairment. Activity reduction is a natural body response to increase in internal body temperature, and a compensatory mechanism to make body balanced. This study was carried out to estimate productivity loss due to heat exposure among Iranian outdoor workers. The study population was entire Iranian outdoor workers in 2014, in different job categories. Method: Heat exposure was calculated using Wet Bulb Globe Temperature using of meteorological data from 83 synoptic stations in 30 Iran’s provinces. Estimation of heat induced productivity loss was done based on graph of “work capacity”. Discussion: The results show that WBGT value reached its highest level during summer, especially in Bushehr (38.87 °C), Khuzestan (38.54 °C), and Sistan-and-Baluchestan (32.51 °C). While, in Chahar-Mahal-and-Bakhtiari (26.55 °C) and West-Azarbaijan (27.25°C) the least values of WBGT was observed. The highest productivity loss occurred during summer with its highest level in two provinces of Khuzestan and Bushehr (96%). In conclusion, by moving from north-west regions toward south-east regions, the level of productivity loss greatly increased. In Iran, the average of productivity loss during summer period is 60%, which is a significantly high value, in terms of climate condition and occupational distribution. Result: Due to the important role of outdoor workers and growing trend of increase in temperature, productivity loss of this working population is undeniable. Adopting preventive strategies to increase compatibility and reduce sensitivity of exposed workers is essential.